Ogilvie’s syndrome - a complication of severe COVID-19 infection - Chong, Collins; Ibrahim, Noor Airini; Abdul Maei, Ngazraini (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
A higher rate of gastrointestinal complications has been shown in COVID-19 patients admitted to the intensive care unit than their counterparts without COVID-19. Ogilvie’s syndrome or acute colonic pseudo-obstruction is described as colonic distension without mechanical obstruction, usually caused by infections, opioid use, renal dysfunction, and electrolyte imbalance. We report a patient with Ogilvie’s syndrome probably secondary to COVID-19. The patient was a 51-year-old man diagnosed as category 5 COVID-19, requiring intensive care treatment and mechanical ventilation. He developed transverse colonic perforation following large bowel dilatation, for which laparotomy and colectomy were done. Unfortunately, he succumbed to death due to intrabdominal sepsis with multiorgan failure. Possible pathogenesis of ileus in severe COVID-19 infection includes viral-induced autonomic nervous system dysfunction, viral-induced gut inflammation mediated by ACE-2 receptors located on the enterocytes, and ischaemic endothelialitis.